SEARCH FOR THE STANDARD MODEL HIGGS-BOSON IN Z(0) DECAYS - Abreu, P; Adam, W; Adye, T; Agasi, E; Ajinenko, I; Aleksan, R; Alekseev, G; Allport, P; Almehed, S; Almeida, F; Alvsvaag, S; Amaldi, U; et al. (1994)
A search for the Standard Model Higgs boson was performed in the data sample of around 1 million hadronic Z0 decays recorded in 1991 and 1992 with the DELPHI detector at LEP. The Higgs boson was searched for through its production in association with either neutrinos, electrons or muons. Four low mass events remain after the selections in the charged leptonic channels, that are likely to be due to background, especially four fermion processes. These results restrict the mass of the Standard Model Higgs boson to be larger than 55.7 GeV/c2 at the 95% confidence level.